2022
DOI: 10.1126/sciadv.abm5164
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic profiling platforms head to head: Leveraging genetics and clinical traits to compare aptamer- and antibody-based methods

Abstract: High-throughput proteomic profiling using antibody or aptamer-based affinity reagents is used increasingly in human studies. However, direct analyses to address the relative strengths and weaknesses of these platforms are lacking. We assessed findings from the SomaScan1.3K ( N = 1301 reagents), the SomaScan5K platform ( N = 4979 reagents), and the Olink Explore ( N = 1472 reagents) profiling techniques in 568 adults from the Jackson Heart … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
72
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(108 citation statements)
references
References 54 publications
5
72
0
Order By: Relevance
“…This suggests that although some pQTLs can be robustly replicated across distinct proteomics methods, aptamer‐ and antibody‐based technologies largely provide non‐overlapping information. A recent large‐scale study directly compared the aptamer‐based SomaScan technology with antibody‐based PEA and found considerable differences in results (Katz et al , 2022 ), which is in accordance with our findings. Importantly, Katz et al ( 2022 ) found evidence supporting more reliable protein target specificity and a higher number of phenotypic associations for the PEA assays, used in the current study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This suggests that although some pQTLs can be robustly replicated across distinct proteomics methods, aptamer‐ and antibody‐based technologies largely provide non‐overlapping information. A recent large‐scale study directly compared the aptamer‐based SomaScan technology with antibody‐based PEA and found considerable differences in results (Katz et al , 2022 ), which is in accordance with our findings. Importantly, Katz et al ( 2022 ) found evidence supporting more reliable protein target specificity and a higher number of phenotypic associations for the PEA assays, used in the current study.…”
Section: Discussionsupporting
confidence: 92%
“…The largest previous study on CSF pQTLs used an aptamer‐based approach (Yang et al , 2021 ). Recent comparisons between aptamer‐ and antibody‐based pQTL studies highlight that the technology used for protein quantification could have a significant impact on the findings, with antibody‐based methods being more specific (Katz et al , 2022 ). Therefore, we attempted to discover both CSF and plasma pQTLs in a large and deeply phenotyped cohort of healthy controls and patients with different neurological diseases, using highly specific biomarker assays to capture a wide range of biological pathways.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Limitations to the study include that Olink protein panels include prespecified proteins of interested compared to other proteomic platforms which allow for the simultaneous measurement of a larger number of proteins, and Olink is relative quantification. However, as evidence for robustness of our assays in orthogonal assessments, we note that five of the 13 proteins in the HFpEF proteomic-model are on the SomaScan platform and are highly correlated with Olink values 51 ; and 11 of the proteins in the 13-protein model have known cis protein quantitative trait loci (pQTL) 51 supporting the binding specificity of the assay for its cognate protein. Future work should validate levels of the protein findings here across alternative technologies and consider serial measurements in prospective studies.…”
Section: Discussionmentioning
confidence: 73%
“… 15 The Olink proximity extension assay (PEA), using affinity proteomics to measure relative protein concentrations in biological materials by qPCR, 16 has gained increasing attention and use in characterizing patterns of proteins in health and disease. 17 , 18 , 19 …”
Section: Introductionmentioning
confidence: 99%